Evangelism as Life‐affirming Activity in the City. (July 2016) - Jackson, Darrell
Abstract: In this article I will reflect on my role as a theological educator as I seek to engage students with the missiological context and challenge of the city, particularly Sydney, Australia. The article assumes that life‐affirming evangelism in the city requires adoption of the posture of a resident stranger in the city; an appreciation for the biblical narratives of creation, fall, redemption, restoration, and the contribution these make to an understanding of God's life‐affirming mission in the city; an openness to the likelihood of multiple and diverse responses to the city; and a commitment to developing life‐affirming practices that are potentially evangelistic. Finally, I reflect on urban and suburban aspiration and consider how this is best engaged by the practice and witness of life‐affirming evangelism.